2022
DOI: 10.21203/rs.3.rs-1513399/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An optimal control model for the transmission dynamics of Lassa fever

Abstract: In this paper, a mathematical model for Lassa fever transmission dynamics with rodent logistic growth is developed and analysed. The stability analysis of the autonomous system of the model is presented. The sensitivity analysis of the parameters is performed using the Partial Rank Correlation Coefficient (PRCC) technique. The non-autonomous model is further analysed for stability of disease-free periodic equilibrium(DFPE) in terms of reproduction number ratio, $R_{0t}.$ It shown that DFPE is locally asympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several studies [5][6][7][8][9][10][11] have used mathematical modeling to understand the various aspects of Lassa fever transmission and dynamics. Ibrahim et al 7 developed a model for Lassa virus transmission; the model includes both human-to-human and rat-to-human transmission modes, along with the vertical transmission within the rat population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [5][6][7][8][9][10][11] have used mathematical modeling to understand the various aspects of Lassa fever transmission and dynamics. Ibrahim et al 7 developed a model for Lassa virus transmission; the model includes both human-to-human and rat-to-human transmission modes, along with the vertical transmission within the rat population.…”
Section: Introductionmentioning
confidence: 99%
“…While reductions in mouse-to-human and human-to-human transmission rates exhibit notable impacts on the infection count, they are deemed insufficient to eradicate the disease. Madubueze and Chazuk 8 formulated Lassa fever model with the aim of implementing optimal control strategies that showed that measures such as proper food handling, utilization of personal protective equipment, treatment, isolation, and control of rodent hunting collectively can significantly alleviate the burden of the disease.…”
Section: Introductionmentioning
confidence: 99%